Sistem Informasi Administrasi Perkara Hukum Perdata Pada Kantor Advokat (Studi Kasus : Buyung & Partners) - Sari, Amy Kartika; Prasetyo, Koko Wahyu (LPPM STIKI MALANG, 2019)
At the Buyung & Partners Law Firm, there are obstacles related to case files, which are getting more and more day by day which can cause the exchange of files, some important data that is missing, damaged files etc. This system discusses filing case files. There are also obstacles in scheduling advocates for trial companions. The two elements above are the most important part in managing legal cases. Therefore an Information System is created that can overcome these obstacles. The Advocate's scheduling scheduling system is an effective solution to overcome the conflicting Advocate's schedule. Notification via email to Advocates and Clients before the trial is considered to help both parties to prepare themselves before going to trial at the District Court. In addition to the two features above, this system also discusses finance managed in the Buyung & Partners Law Firm. Financial management concerns the payment of case handling fees by clients, the distribution of honorarium for lawyers and the income received by the office.